2011
DOI: 10.5539/mas.v5n4p11
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Moulded Laminated Veneer Oil Palm (MLVOP)

Abstract: This research was undertaken to study the suitability of oil palm trunk to be utilized as a raw material for moulded laminated veneer oil palm (MLVOP). The trunks were converted into veneers by rotary peeling machine. The veneers were segregated into two veneer qualities namely superior (S) and inferior (I). The methods of segregating veneers quality were defined. The superior veneers were obtained by peeling the billets until their diameters left approximately 12 inches, meanwhile the inferior veneers were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Statistical data show that 40 million tons residual oil palm biomass wastes from oil palm trees such as EFB, OPT, OPF, and PPF are produced every year in Malaysia (Baharuddin et al 2009). Based on this research, only 10% of the total oil palm biomass is used, while the remaining 90% is underutilized (Khalil and Bhat 2010;Khalil et al 2011). Cellulosic raw materials produced from both dried coconut trunks and OPF can be used as alternatives to wood materials (Khalil and Rozman 2004;Amouzgar et al 2010).…”
Section: Oil Palm Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical data show that 40 million tons residual oil palm biomass wastes from oil palm trees such as EFB, OPT, OPF, and PPF are produced every year in Malaysia (Baharuddin et al 2009). Based on this research, only 10% of the total oil palm biomass is used, while the remaining 90% is underutilized (Khalil and Bhat 2010;Khalil et al 2011). Cellulosic raw materials produced from both dried coconut trunks and OPF can be used as alternatives to wood materials (Khalil and Rozman 2004;Amouzgar et al 2010).…”
Section: Oil Palm Biomassmentioning
confidence: 99%
“… Wood fiber-plastic composite  Wood fiber-agricultural fiber composite possesses better machining parameters and improves the efficiency of the use of raw materials (Bhat et al 2010). Innovative research combining both EFB and OPT produced a new blend of plywood with improved quality relative to existing plywood, particularly regarding flexural strength, screw withdrawal, and shear strength (Salleh et al 2011;Khalil et al 2010c;Khalil and Rozman 2004). For example, studies using oil palm trunks to produce molded laminated veneer oil palm (MLVOP) for furniture demonstrated that that MLVOP performed similarly to or better than normal wood veneer, and was suitable for making profitable furniture products.…”
Section: Wood-non Wood Compositementioning
confidence: 99%
See 1 more Smart Citation